2022
DOI: 10.1055/a-1925-2210
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of State-Mandated Third Trimester Repeat HIV Testing in a Large Tertiary Care Center

Abstract: Objective: The Illinois Perinatal HIV Prevention Act was passed to ensure universal HIV testing once during pregnancy and was extended in 2018 to add third trimester repeat HIV screening. The objectives of this analysis were to describe uptake of, and patient factors associated with, third trimester repeat HIV testing at a high-volume birthing center. Study Design: This is a retrospective cohort study of people who delivered at a single tertiary care hospital in Illinois during 2018. Women who delivered befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Our results are like previous studies in some jurisdictions that have shown that most women get tested during pregnancy, but that universal testing is not reported consistently, as recommended. 12 Evidence from self-reported survey data and chart review studies suggests that in recent years in the areas covered by these studies, 57%-81% of women have been tested for HIV during pregnancy. 17,18 However, prenatal testing rates for sexually transmitted infections (STIs), such as syphilis, and rubella and hepatitis B, have been found to be 97% or higher.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results are like previous studies in some jurisdictions that have shown that most women get tested during pregnancy, but that universal testing is not reported consistently, as recommended. 12 Evidence from self-reported survey data and chart review studies suggests that in recent years in the areas covered by these studies, 57%-81% of women have been tested for HIV during pregnancy. 17,18 However, prenatal testing rates for sexually transmitted infections (STIs), such as syphilis, and rubella and hepatitis B, have been found to be 97% or higher.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are like previous studies in some jurisdictions that have shown that most women get tested during pregnancy, but that universal testing is not reported consistently, as recommended. 12 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations